Study of Adenine Aminohydrolase in the Yeast, Schizosaccharomyces pombe - Abbondandolo, Angelo (1971)
Observation of the growth of some adenineless mutants of Schizosaccharomyces pombe on six substituted purine analogs leads to the hypothesis that an enzyme is present which catalyzes the conversion of these analogs into hypoxanthine. The enzyme adenase (adenine aminohydrolase, EC 3.5.4.2) has been found to be active in cell-free extracts of S. pombe. Results are reported which are in agreement with the hypothesis that this enzyme is responsible for the in vivo utilization of 6-chloropurine. This evidence comes mainly from a study of adenine aminohydrolase in two mutants selected for partial inability to grow on 6-chloropurine.